Military nuclear mess - Baker, Glenn (Washington : Center for Defense Information, 1998)
Worldwide, the problem of radioactive military waste is reaching catastrophic proportions. The Waste Isolation Pilot Program in New Mexico is the American military's solution to the problem of safe disposal of nuclear waste
Executive producer, Gene R. LA Rocque
Narrator: Rear Admiral Eugene Carroll
Keywords: Radioactive waste disposal in the ground; Radioactice waste disposal